PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SUPLEMEN KESEHATAN K-OMEGA SQUA (Studi Kasus pada Stokis PT K-LINK Nusantara Cabang Plaju Palembang) - Heri Setiawan; Yusleli Herawati; Santi Asmarani (Politeknik Negeri Sriwijaya, 2015)
The aim of this research is to know the influence of price and the quality of product on customer’s buying decision of health supplement K-Omega Squa. The data were collected from questionnaires to 98 customers, and interviews with buyer of PT K-Link Nusantara Plaju branch Palembang. Data were analyzed by Statistical Product and Service Solution with linier regression formula, correlation and determination coefficient. Independent variables in this research are price and quality of product, and dependent variable is buying decision. The result showed that determination coefficient (R Square) was 87,2 % affected by price and the quality of product then 12,8% were affected by other variables. The result shows that simultaneously price and quality of product have significant effect on customer’s buying decision. The result shows that partially price have significant effect on buying decision. quality of product have significant effect on buying decision.